ANALISIS BIAYA PENDIDIKAN DENGAN PENDEKATAN ACTIVITY BASED COSTING SYSTEM : STUDI KASUS PADA JURUSAN ELEKTRO FAKULTAS TEKNOLOGI INDUSTRI INSTITUT TEKNOLOGI SEPULUH NOPEMBER SURABAYA - , Agus Dwi Purwolastono, SE. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Colleges are institutions or organisations or public sector company engaged in the field of services, with its main product is the service of education. Colleges generally determine the cost of education with a very simple method. It is considered reasonable because the College has always been synonymous with a cheap cost for assistance and subsidy funds from the Government but remained charged produce graduates who qualified. Institute of Technology Sepuluh Nopember gaining the status of Badan Layanan Umum (BLU) from the Ministry of Finance on the basis of A decision of the Minister of Finance of Indonesia no. 363/KMK.05/2008, December 17, 2008. As the institution that implements Pengelolaan Keuangan (PK) Badan Layanan Umum (BLU), tariff services calculation to the community is very important. It is contained in the Government Regulation no. 23/2005 on Pengelolaan Keuangan Badan Layanan Umum (PKBLU), where tariff calculation for service fees BLU listed in article 9. By trying to show the same principle, activity based costing (ABC) can be applied in the management of higher education as a determination of the standard fees. Research conducted at the Department of Electrical Engineering Faculty of Industrial Technology Institute of Technology Sepuluh November. In doing this research, the author aims to find out the ratio of the ABC system approach and the conventional system approach in the imposition of indirect costs to support the calculation of the cost of educational services that are more accurate. The research method is done with descriptive analysis method of describing of the object to the actual research by means to collect relevant data are available, then compiled, studied, and analyzed further. Based on the results of the discussion is that by using the ABC System, the cost of activities charged to the services on the basis of consumption activities by each service. ABC system has various kinds of cost drivers, where the cost driver is not only based on the number of students, but also based on the extensive amount of research, spacious room of education, the number of computer and lecturer. Calculation of the cost of education use the ABC system produces educational costs rates more accurate compared to use of the calculation of the cost of education with the conventional method of approach.